Strategic management of organizations and stakeholders : concepts and cases - Harrison, Jeffrey S.; John, Caron H. St. (Cincinnati, Ohio : South-Western College, 1998)
Strategic management and environmental analysis: Stakeholders and the Strategic management process; the broad environment; the operating environment and external stakerholders. Organizational analysis and strategic direction: the internal environment and competitive advantage; strategic direction. Strategy formulation: business-level strategy; Corporate-level strategy. Strategy implementation and control: strategy implementation; strategic control; corporate restructuring; preparing a case analysis.
Keywords: Strategic planning; Industrial management; Industrial management; Strategic planning